Sociological Aspects of the Party and Political Life of the Community - Ismoilova Nigorakhon Usmonjonovna (Genius Journals, 2022)
The article reveals the role and social status of women in society. Information is given that a woman in modern society has a completely different status and vocation, she has other values and needs that make us reconsider our views on the female role in today's world. The historiography of sources considering the women's issue is also given
Keywords: Woman; Social Status; Gender Asymmetry; Gender Analysis